THE EFFECT OF INTERNAL CONTROL SYSTEM, APPARATUS COMPETENCE, INTERNAL SUPERVISION ON ACCOUNTABILITY AND PERFORMANCE OF FINANCIAL MANAGERS OF MAKASSAR CITY GOVERNMENT - Yuyu Ruhayu; Salim Basalamah; Baharuddin Semmaila; Muhsin Wahid (Universitas Muhammadiyah Luwuk Banggai, 2022)
This study was conducted to analyze the influence of leadership, Islamic motivation, and organizational commitment on job satisfaction, analyze the effect of job satisfaction on performance, analyze the influence of leadership, Islamic motivation, and organizational commitment on performance, analyze the influence of leadership, Islamic motivation, and commitment to performance through job satisfaction. The object of this research is the Land Agency Office of Gowa Regency with a total sample of 125 employees from a population of 182 employees (based on position). This sample was taken based on the probability sampling technique with the purposive sampling method. The data were analyzed using the AMOS SEM program. The results of this study indicate that leadership style has a positive and significant effect on job satisfaction, Islamic motivation has a positive and significant effect on job satisfaction, organizational commitment has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on performance, leadership style has a positive and significant effect on performance, Islamic motivation has a positive and significant effect on performance, organizational commitment has a positive and insignificant effect on performance, leadership style through job satisfaction has a positive and insignificant effect on performance, Islamic motivation has a positive and significant effect on performance through job satisfaction, and organizational commitment has an effect positive is not significant on performance